2013
DOI: 10.3126/banko.v23i1.9465
|View full text |Cite
|
Sign up to set email alerts
|

Revenue distribution pattern and park-people conflict in Chitwan National Park, Nepal

Abstract: This study has assessed patterns and consequences of park revenue sharing and implementation effectiveness to reduce park-people conflict in the Buffer Zone of Chitwan National Park. To explore programme implementation practice and consequences, two-thirds (n=14) of user committees were selected from the four management sectors. From the sampled committees, a questionnaire survey was randomly taken from user groups (n=100) to collect income and expenditure data. The revenue disbursement trends were favoured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…Within this range, Rhinoceros unicornis occupies an area of 7,240 km 2 , which is 5.01% of the total area of the country. Similarly, our model predicted the distribution of species from the buffer zone of CNP where there is the problem of human-rhino conflict (57,58). In addition to this, the model also predicted the distribution of species in the Eastern region of Nepal (Rautahat and Sarlahi).…”
Section: Discussionmentioning
confidence: 87%
“…Within this range, Rhinoceros unicornis occupies an area of 7,240 km 2 , which is 5.01% of the total area of the country. Similarly, our model predicted the distribution of species from the buffer zone of CNP where there is the problem of human-rhino conflict (57,58). In addition to this, the model also predicted the distribution of species in the Eastern region of Nepal (Rautahat and Sarlahi).…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that these activities have helped to improve the livelihoods of some of the pastoral communities in the study area, in addition to improving rangeland management to some extent. Other studies in Nepal have also reported enhanced livelihoods of buffer zone communities due to: Income diversification, capacity enhancement, resource conservation, ecotourism promotion, increased farm production, and reduced conflict between Park authorities and communities through revenue distribution schemes [43][44][45].…”
Section: National Policy and Institutional Frameworkmentioning
confidence: 92%
“…According to the US Geological Survey, human-wildlife conflicts occur due to increased human ambitions, and consequently threaten the safety and survival of wildlife [5]. Some wildlife species, such as large carnivores and mega-herbivores, cause considerable harm to the people, as well as damage to their properties [4,[6][7][8][9][10][11]. The damages result in people's negative attitudes toward the species responsible for the losses [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some wildlife species, such as large carnivores and mega-herbivores, cause considerable harm to the people, as well as damage to their properties [4,[6][7][8][9][10][11]. The damages result in people's negative attitudes toward the species responsible for the losses [10][11][12][13][14]. Conflicts or co-existence between human and wildlife are influenced by a complex interaction of numerous factors, including biological, geographic, political, social, institutional, financial, cultural, and historical features [4].…”
Section: Introductionmentioning
confidence: 99%